Password-based authenticated key distribution in the three-party setting with forward security. (4th August 2009) - Wu, Shuhua; Zhu, Yuefei
Key establishment protocols are used for distributing shared keying material in a secure manner. In 1995, Bellare and Rogaway presented a three-party server-based key distribution (3PKD) protocol. But the protocol was recently found insecure and then was fixed by Choo et al. (2005b). But forward-secrecy is not considered in the revised protocol. In this paper, we demonstrate that it is not forward secure indeed. We then revise the protocol to be a password-based authenticated key distribution in the three-party setting and prove our protocol is forward secure in the random-oracle and ideal-cipher models under the password-based chosen-basis gap Diffie-Hellman assumption. Our protocol is quite simple and elegant, and rather efficient when compared to previous solutions.